Answer:
8
Explanation:
Remember the phrase "power to a power means to multiply the exponents"
That is, if you have a number (call it x) raised to a power (call it b), and that whole expression is raised to a power (call it c), it's the same as that number x raised to the power of the product of those two powers.
![(x^a)^b = x^a^b](https://img.qammunity.org/2022/formulas/mathematics/college/gkkczjyvll601o9kc678zaps8c13rpzvoj.png)
Here's an example showing to give some intuition behind this (and a way to derive the above formula if you forget it):
![x^3 = x*x*x\\(x^3)^2 = (x*x*x)^2 = x*x*x*x*x*x = x^6](https://img.qammunity.org/2022/formulas/mathematics/college/xie1ail2f0c22un5inhqt6mxqn30mw7ics.png)
Or more simply,
![(x^3)^2 = x^(^3^*^2^) = x^6](https://img.qammunity.org/2022/formulas/mathematics/college/6ddpxymcertkwgo91iop3nne6m82jrzvlg.png)
So in this case:
(remember a number raised the to the power of 1/2 is the square root of the number; in this case, the square root of 64 is 8)